Perempuan Bali dalam Pengelolaan Pariwisata di Bali - Dewa Putu Oka Prasiasa; Yeyen Komalasari; Dewa Ayu Diyah Sri Widari (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2023)
Women are often positioned as marginal people in various fields of life, including the position of Balinese women in managing tourism in Bali. This article aims to analyze the position of Balinese women in tourism management in Bali. This research is a literature study with a qualitative descriptive analysis. This research found that Balinese women are very enthusiastic as homeworkers because they are related to domestic activities. These symptoms are related to the ideological superstructure and work ethic. This study also found that social structure and material infrastructure strengthen the work ethic. Balinese women think that work is yadnya, needs to be carried out and practiced to improve self-quality. Even though Balinese women experience injustice in the management of tourism in Bali, they are still eager to earn a living. Abstrak Perempuan sering diposisikan sebagai kaum marginal dalam berbagai bidang kehidupan, termasuk posisi perempuan Bali dalam pengelolaan pariwisata di Bali. Artikel ini bertujuan menganalisis posisi perempuan Bali dalam pengelolaan pariwisata di Bali. Penelitian ini merupakan studi literatur dengan analisis deskriptif kualitatif. Penelitian ini menemukan perempuan Bali amat bergairah sebagai pekerja rumahan karena berkaitan dengan kegiatan domestik. Gejala ini terkait dengan superstruktur ideologi dan etos kerja. Penelitian ini juga menemukan struktur sosial dan infrastruktur material memberikan penguatan terhadap etos kerja. Perempuan Bali menganggap kerja adalah yadnya, perlu dilaksanakan serta diamalkan untuk peningkatan kualitas diri. Meskipun perempuan Bali mengalami ketidakadilan dalam pengelolaan pariwisata di Bali, namun mereka tetap bersemangat untuk memperoleh nafkah.